Pengaruh Konservatisme Akuntansi, Profitabilitas, Growth Opportunities, Ukuran Perusahaan dan Leverage Terhadap Earning Response Coefficient (Studi pada Perusahaan Sektor Properti dan Real Estate yang Terdaftar di Bursa Efek Indonesia Tahun 2019–2021) - Miske Wananda; Fitriasuri Fitriasuri (Universitas Batanghari Jambi, 2023)
This study aims to find out wether the Earning Response Coefficient (ERC) is influenced by Accounting Conservatism, Profitability, Growth Opportunities, Company Size, and Leverage in real estate and property companies whose names are listed on the Indonesia Stock Exchange for the 2019-2021 period. This study applied a purposive sampling technique, namely with a sample consisting of 35 companies and a population of 73 companies. This study applies multiple regression analysis techniques using SPSS 22. Based on the results in this study, it can be stated that the 2019-2021 ERC is not affected by the variables Accounting Conservatism, Growth Opportunities, Company Size, and Leverage have no effect on ERC 2019-2021, while ERC is only influenced by the variable Profitability.